Access to loans and local development: Evidence from Brazilian municipalities - Renata Motta Café (Inter-American Development Bank (IDB), 2024)
Limited access to credit has been identified as a major constraint to sustainable municipal development, but empirical evidence on the effectiveness of credit operations remains inconclusive. This paper evaluates the impact of federal government guaranteed loans on public expenditures. Using data from Brazilian municipalities and a regression discontinuity design that leverages a discontinuity in the eligibility criteria for federal government guarantees, I show that the loans have a positive impact on the quality of local expenditure and social outcome indicators. This impact is characterized by a significant increase in investment while keeping personnel expenditures stable.
Keywords: H71; H75; R51; 330; state capacity; access to credit; public expenditure; municipal development